Fabrication of calixarene-grafted magnetic nanocomposite for the effective removal of lead(II) from aqueous solution. Issue 19 (24th August 2019) - Kamboh, Muhammad Afzal; Wan Ibrahim, Wan Aini; Rashidi Nodeh, Hamid; Zardari, Liaquat Ali; Sanagi, Mohd Marsin
ABSTRACT: Magnetic nanocomposites adorned with calixarene were successfully prepared by immobilizing diethanolamine functionalized p-tert -butylcalix[4]arene (DEA-Calix) onto silica-coated magnetic nanoparticles (MNPs). The synthesis, surface morphology, purity, elemental composition and thermal stability of newly prepared nanocomposites were analyzed using FT-IR spectroscopy, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDX), X-ray diffractometer (XRD), thermal gravimetric analysis (TGA) and vibrating sample magnetometer (VSM). Magnetic solid-phase adsorption (MSPA) was employed to explore the adsorption behavior of DEA-Calix-MNPs towards Pb(II) from water samples prior to its flame atomic absorption spectrometric analysis. The essential analytical factors governing the adsorption efficiency such as solution pH, mass of adsorbent, concentration and contact time have been investigated and optimized. The results depict that DEA-Calix-MNPs has excellent adsorption efficiency 97% (at pH 5.5) with high adsorption capacity of 51.81 mg g –1 for Pb(II) adsorption. Additionally, kinetic and equilibrium studies suggested that Pb(II) adsorption process follows a pseudo-second-order model and Langmuir isotherms, respectively. Real sample analysis also confirmed field applicability of the new DEA-Calix-MNPs adsorbent.